2020
DOI: 10.1038/s41598-020-73281-z
|View full text |Cite
|
Sign up to set email alerts
|

The tissue specific regulation of miR22 expression in the lung and brain by ribosomal protein L29

Abstract: Endogenous miR22 is associated with a diverse range of biological processes through post-translational modification of gene expression and its deregulation results in various diseases including cancer. Its expression is usually tissue or cell-specific, however, the reasons behind this tissue or cell specificity are not clearly outlined till-date. Therefore, our keen interest was to investigate the mechanisms of tissue or cell-specific expression of miR22. In the current study, miR22 expression showed a tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…MiR-22 expression is highly specific to the tissue or cell, but the molecular mechanisms ensuring this expression specificity are unclear [ 63 , 64 ]. MiR-22 is also differentially expressed in distinct human cancers [ 65 ] and downregulated in HCC, but the underlying molecular mechanisms of this decrease remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-22 expression is highly specific to the tissue or cell, but the molecular mechanisms ensuring this expression specificity are unclear [ 63 , 64 ]. MiR-22 is also differentially expressed in distinct human cancers [ 65 ] and downregulated in HCC, but the underlying molecular mechanisms of this decrease remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines, e.g., IL-1α [ 36 ], or metabolites, such as extracellular ATP/UTP [ 76 ], can also impact its expression. The ribosome protein L29 (RPL29) was also reported as an intracellular factor regulating miR-22 levels [ 64 ]. Finally, several studies indicated that the expression of miR-22 is regulated transcriptionally, along with its host gene, by numerous transcription factors including NF-κB [ 77 ], p53 [ 78 ], Fos-B [ 66 ], c-Fos [ 79 ], PU.1 [ 80 ], STAT3 [ 81 ], STAT5 [ 81 ], Nrf1α, and Nrf2 [ 82 ].…”
Section: Discussionmentioning
confidence: 99%